Empathy in Global Business - Verner Worm; Michael Jakobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2018)
This paper analyses the concept of empathy in multinational organizations. In the 21st century "You need to be soft to get hard results!" as McDonald (2008) aptly stated. Based on contextual changes in both costumer clienteles and among younger employees, empathy or compassion is becoming central concepts in international business. We analyses the concept of empathy in a global context describing it mainly from a phenomenological perspective, but also introduce other approaches for comparative and informative reasons. After having defined empathy as consisting of three elements i.e. know yourself, know the other and create positive communication, we focus on intentional mode of understanding involving envisaging the actions and emotions of 'the other'. Empathy, triggered and mediated by various social encounters, assume different form and encompassing an array of possibilities for interpersonal understanding depending on the constitution of a given context. Based on this we analyze Maersk Line's organizational culture and how employees navigate it accordingly.
hdl:10398/9670
Keywords: 330; Empathy; Phenomenology; Organizational cultures; Employee navigation; Maersk Line; Multinationales Unternehmen; Emotion; Unternehmenskultur; Phänomenologie; Dänemark